2017
DOI: 10.1186/s12913-017-2018-5
|View full text |Cite
|
Sign up to set email alerts
|

A catalyst for system change: a case study of child health network formation, evolution and sustainability in Canada

Abstract: BackgroundThe purpose of this study was to examine key processes and supportive and inhibiting factors involved in the development, evolution, and sustainability of a child health network in rural Canada. This study contributes to a relatively new research agenda aimed at understanding inter-organizational and cross-sectoral health networks. These networks encourage collaboration focusing on complex issues impacting health – issues that individual agencies cannot effectively address alone. This paper presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 86 publications
0
29
0
5
Order By: Relevance
“…Power imbalances and conflicts: Perceived or real power asymmetries can become a strong barrier to inter-organisational collaboration and affect collaboration outcomes [2358]. For instance, the dependence of one organisation on another can work as a barrier if the more powerful organisation does not provide the necessary input [59].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Power imbalances and conflicts: Perceived or real power asymmetries can become a strong barrier to inter-organisational collaboration and affect collaboration outcomes [2358]. For instance, the dependence of one organisation on another can work as a barrier if the more powerful organisation does not provide the necessary input [59].…”
Section: Resultsmentioning
confidence: 99%
“…In case of power imbalances organisations often start to defend their own resources and authority, which often leads to power conflicts [5760]. Power imbalances can also slow down planning and committee work in health service networks [58]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the NHS Clinical Networks). Various case studies indeed suggest that governmental policy can operate as an important catalyst for HCN formation [2829]. Another relevant example of such policy is Belgium, where the government is developing policy that would legally require all Belgian hospitals to become part of a single larger hospital network.…”
Section: Mechanisms Of Coordination (Government Markets and Civil Smentioning
confidence: 99%
“…One example is that of a Canadian child health network which worked, successfully, in close collaboration with the provincial department of Health Staff. However, it was also reported that ‘at times the provincial staff tried to control the Network strategic agenda and micromanaged key shared projects’ [29]. A respondent reported that this ‘really caused a lot of problems’ [29].…”
Section: Justification For a Proper Balancementioning
confidence: 99%